Electrodialytic processes in solid matrices. New insights into batteries recycling. A review. - Villén-Guzmán, María Dolores; Arhoun, Brahim; Vereda-Alonso, Carlos; Gómez-Lahoz, César; Rodríguez-Maroto, José Miguel; Paz-García, Juan Manuel (My University, 2019)
Electrodialytic Remediation has been widely applied to the recovery of different contaminants from numerous solid matrices solving emerging issues of environmental concern. Results and conclusions reported in studies about real contaminated matrices are summarizes in this work. The influence of the pH value on the treatment effectiveness has been widely proved highlighting the phenomenon “water splitting” in the membrane surface. This dissociation of water molecules is related to the “limiting current” which is desirable to be exceed at the Anion Exchange Membrane in order to produce the entering of protons toward solid matrix. Other important parameters for the optimization of the technique, such as the current density and the liquid to solid ratio, are also discussed through the revision of studies using real solid matrices. This work also focusses on the pioneer proposal of electrokinetic technologies for the recycling of lithium ion batteries considering the relevance of waste properties in the design and optimization of the technique. From a thorough literature revision, it could be concluded that further experimental results are needed to allow an optimal application of the technique to the rising problem of residues from batteries. The main aim of this work is to take the first steps in the recovery of valuable metals from spent batteries, such as Li and Co, incorporating principles of green chemistry.
Keywords: Electroquímica; Membranas (Biología); Environmental Remediation; Waste treatment and Waste Minimization; Membranes; Electrochemistry